MENINGKATKAN KEMAMPUAN KOMUNIKASI KARYAWAN PT X DENGAN PROGRAM BEDAH BUKU - Michael Cengkiawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Even though times have changed a lot, soft skills are still needed by employees so that they can develop themselves both personally and professionally. Soft skills are socio-emotional abilities that are important for personal and professional development. Soft skills are usually the opposite of certain technical skills. One of the important soft skills to bemastered by employees is communication skills because communication always occurs in everyday life. Effective communication can make a job easier. Employees in PT X's manufacturing are more technically capable, this is because they are more often involved in machine operations. Therefore, the purpose of this book review program is to hone the employee's communication skills and speaking skills in front of many people. In addition to these objectives, this program is expected to provide additional insight to other employees according to the topic of the book being discussed. This program was held on November 5th, 2021 and was attended by employees from the manufacturing team of PT. X. The responses given by the participants, both for presenters and for the book review program, were quite positive. This can be seen from the evaluation form distributed at the end of the event. Hopefully, this article can be a reference for other parties who want to implement the same program.